Leveling the playing field: a developmental psychologist's perspective - Nesi, Danielle (The Routledge international handbook of juvenile homicide, 2024)
A large body of research demonstrates that youth who engage in violence, including murder, experience high levels of trauma and adversity. These experiences are especially damaging in the context of the absence of protective factors that can buffer the damaging effects of early adversity and foster resilience. Informed by decades of experience interviewing individuals who engaged in violent crimes during their youth, the current chapter provides a forensic, developmental perspective on youth at risk for violence and outlines ways to “level the playing field” for this population. Using Bronfenbrenner’s ecological systems theory as a framework, the current chapter discusses interventions and structural changes needed to foster positive development and resilience among those especially vulnerable for engaging in violence.